The Effect of Project Bases Learning Model With Learning Colaborative Toward Student’s Achievement - Suyanti, Retno Dwi; Br Karo, Desnapia Nesrani; Sitompul, Nopita (Universitas Negeri Padang, 2022)
This research has the purpose to know the student’s achievement in Acid-Base topic by implementing Project Based Learning model. The population of this research are all Senior High School students grade XI in Berastagi , which the samples are 2 classes XIth grade chosen by purposive sampling. 1st as experiment class was taught by Project Based Learning Model while 2nd class as control class was taught by Conventional model. The instrument test had been standardized by expert validator and empiric validity process. The result of test standardization is 20 multiple choice questions with reliability 0.865 . The research resulted that the data is normal distributed and samples are homogenous. The result data showed that student’s achievement taught by Project based learning with lesson study gave higher significance different compared with student’s achievement taught by conventional model. The statement supported by the result of hypothesis testing is t count (5.78) > t table (1.67).